New Zealand's new government: soft power a casualty of coalition politics? - Rogerson, Evan (2024)
In the New Zealand general election of October 2020, the centre-left Labour Party won an absolute majority. This year, in a striking reversal, Labour was swept from power. The new government sworn in on 27 November is a three-party coalition led by the centre-right National Party, with the libertarian ACT party and the populist NZ First. The new government’s focus is very much domestic, with a strong emphasis on reversing measures taken under Labour. The consequences of domestic policy decisions by the Coalition threaten to weaken New Zealand’s “soft power” and its capacity to be an active partner in areas such as climate change and support for multilateralism.